A Novel Structure of Multilayer SIW Filter And Patch Antenna - Zakaria, Zahriladha; Sam , Weng Yik; Abd Aziz, Mohamad Zoinol Abidin; Mutalib, Mohamad Ariffin; Haron, Nor Zaidi (2013)
This paper presents the investigation based upon the resonant circuit approach to distinguish in between the microwave filter and antenna from the equivalent circuit to physical layout where this system is used to reduce the overall volume of RF front-end subsystem especially in wireless communication systems. The physical layouts of the Substrate Integrated Waveguide (SIW) filter and microstrip patch antenna based on single-mode is established based on multilayer technique. This study focuses on the integrated rectangular SIW filter with rectangular microstrip patch antenna to produce radiating and filtering system in a single device. To prove the concept of microwave filter and antenna, the operating centre frequency of 2 GHz is demonstrated and validated through simulation and measurement. The experimental shows promising results and in-line with the simulated results. This study is useful for any microwave system design where the reduction of overall physical volume and weight as well as cost is very important such as in base stations.